การจัดการร้านอาหารภายใต้มาตรฐานอาหารฮาลาลใน 3 จังหวัดชายแดนภาคใต้ - แก้วนุ้ย, ณัจยา; วงศ์วนิชทวี, เฉลิมเกียรติ; ศิลาลาย, ณัฏฐิกา (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 30 No 3 (2562): Academic Services Journal, Prince of Songkla UniversityDO - 10.14456/asj-psu.2019.46, 2019)
การศึกษาวิจัยครั้งนี้ใช้ระเบียบวิธีวิจัยเชิงคุณภาพเพื่อศึกษาการจัดการร้านอาหารภายใต้มาตรฐานอาหารฮาลาลใน 3 จังหวัดชายแดนภาคใต้ โดยมีวัตถุประสงค์เพื่อศึกษาปัญหาและอุปสรรคการจัดการร้านอาหารภายใต้มาตรฐานอาหารฮาลาลและเพื่อเสนอแนวทางการจัดการร้านอาหารภายใต้มาตรฐานอาหารฮาลาลใน 3 จังหวัดชายแดนภาคใต้ของประเทศไทย ในการศึกษาครั้งนี้กลุ่มเป้าหมายในการให้ข้อมูล ประกอบด้วย ผู้ประกอบการร้านอาหารที่ขอตราฮาลาลรับรองมาตรฐานอาหารต่อเนื่องกันอย่างน้อย 3 ปี จำนวน 13 คน ผู้ประกอบการร้านอาหารที่ไม่ขอตราฮาลาลรับรองมาตรฐานอาหาร จำนวน 15 คน ด้วยการสัมภาษณ์เชิงลึกและกลุ่มนักวิชาการหรือผู้เชี่ยวชาญ จำนวน 5 ท่าน ทางด้านสาธาณสุขศาสตร์ และกรรมการสมาคมธุรกิจอาหาร ด้วยการจัดทำประชุมกลุ่มผ่านการทำเวทีรับฟังความคิดเห็น (expert forum) ทำการวิเคราะห์ข้อมูลโดยใช้การวิเคราะห์เนื้อหา และผลการศึกษาได้นำแนวทฤษฎี POLC มาใช้ในการวิเคราะห์ปัญหา และเพื่อหาแนวทางในการจัดการร้านอาหารภายใต้มาตรฐานฮาลาล โดยผลจากการวิเคราะห์ปัญหา พบว่า ร้านอาหารที่ไม่ขอรับรองตราฮาลาล อันเนื่องมาจากการที่ร้านอาหารไม่ทราบรายละเอียดเกี่ยวกับระบบและขั้นตอนต่างๆ ในการขอรับรองมาตรฐานอาหารฮาลาล ใช้เวลาค่อนข้างนานในกระบวนการขอตราฮาลาล และอายุของตราฮาลาลมีระยะเวลาในการใช้สั้นเกินไป อีกทั้งร้านอาหารไม่ได้ให้ความสำคัญกับการมีตราฮาลาลในร้าน เนื่องจากบริบทสังคมและวัฒนธรรมใน 3 จังหวัดชายแดนใต้ที่เจ้าของร้านเป็นชาวมุสลิม จึงได้รับการเชื่อถือจากผู้บริโภคในพื้นที่นั้นๆ อยู่แล้ว ซึ่งจากปัญหาดังกล่าวจึงได้มีการจัดหาแนวทางในการจัดการให้ร้านอาหารใน 3 จังหวัดชายแดนใต้ได้รับตราฮาลาล เพื่อสร้างความเชื่อมั่นแก่ผู้บริโภคทั่วไป โดยแนวทางที่ได้มีดังนี้ คือ ด้านการวางแผน ควรให้ความรู้และความเข้าใจที่ถูกต้องเกี่ยวกับหลักฮาลาล ทั้งกระบวนการขอรับรองมาตรฐานฮาลาล ควรมีการวางแผนเรื่องเงินทุนหมุนเวียนในการจัดการร้านอาหาร เพื่อให้เพียงพอต่อการบริหารงานได้อย่างราบรื่น ด้านการจัดการองค์การ ควรมีการจัดโครงสร้างของร้านที่เป็นระบบ รวมทั้งข้อกำหนดของการบริหารและการอยู่ร่วมกันในองค์กรอย่างชัดเจน และควรมีกลไกและมาตรการของรัฐเข้ามาช่วยส่งเสริมยกระดับธุรกิจที่เกี่ยวข้องกับอาหารฮาลาล เพื่อให้ร้านอาหารฮาลาลได้เล็งเห็นถึงความสำคัญของตราฮาลาลมากขึ้น ในด้านการควบคุม ควรมีการกำหนดระเบียบเกี่ยวกับมาตรฐานอาหารฮาลาล เพื่อให้กระบวนการจัดหาวัตถุดิบ กระบวนการผลิต และการบริการถูกต้องตามบทบัญญัติศาสนาอิสลาม ข้อกำหนดการรับรองมาตรฐานอาหารฮาลาลและถูกสุขอนามัย คำสำคัญ: การจัดการ POLC, มาตรฐานอาหารฮาลาล, ร้านอาหารภายใต้มาตรฐานอาหารฮาลาล, สามจังหวัดชายแดนภาคใต้   This research was a study on restaurant management under certified Halal food standard in three Southern border provinces of Thailand. This study was aimed to study on restaurant management problems under Halal food standards and to recommend guidelines for managing restaurants under Halal food standards in the three Southern border provinces of Thailand. In this study, the target groups providing information consisted of 13 informants from restaurant entrepreneur requesting Halal brand certification for food standards at least 3 years, and 15 informants from restaurant entrepreneur that do not have a Halal brand with an in-depth interview technique and a group of 5 experts with a focus group through the expert forum for data analysis. For results of the study, POLC theory was used to analyze the problems and find the ways to manage restaurants under the Halal standard. From the result analysis indicated that shops did not request Halal branding since they did not the details of procedures for Halal food standard applying and a long-time applying process. In addition, the restaurant did not give attention for the Halal brand in the store due to the social and cultural context in the three southern border provinces that the shop owners were Muslim. Therefore, they were trusted by consumers in these specific areas. As a result of this problem, the guidelines for management of restaurants in the three southern border provinces have been received in order to create confidence among consumers in general. The guidelines were following as: In planning perspective, providing knowledge and correct understanding about the Halal principles including Halal certification, and planning money and budgets for working in restaurant management in order to be sufficient to manage smoothly in the organizational management. In organizing perspective, there should be a systematic structure of the shop including clear management and coexistence requirements in the organization. It should also have systems and mechanisms to help promote the business related to Halal food so that Halal restaurants give more attention for the importance of Halal branding. In control perspective, it should have a regulation regarding Halal food standards in order to provide the raw material, production and service according to Islamic provisions Halal food standards as well as personal hygienic requirements. Keywords: POLC management, certified Halal food standard, restaurant under certified Halal food, three southern border provinces